1999
DOI: 10.1046/j.1365-2249.1999.00917.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of soluble membrane cofactor protein (CD46, MCP) in patients with systemic lupus erythematosus (SLE)

Abstract: SUMMARYMembrane cofactor protein (MCP, CD46) is a cell surface complement regulatory protein which acts as a cofactor for the factor I-mediated cleavage of the activated complement components C3b/C4b. To evaluate the clinical usefulness of serum soluble CD46 as a marker of disease activity in patients with SLE, serum levels of sCD46 were measured by ELISA, using two MoAbs (M160 and M177), each of which recognized two different epitopes on CD46 molecule in SLE, other autoimmune diseases and healthy controls. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 23 publications
4
40
2
Order By: Relevance
“…Another report (29) has suggested that tubular MCP is overexpressed at the deposition site of the membrane attack complex. The levels of sMCP were increased in patients with malignancy (19) and autoimmune diseases such as systemic lupus erythematosus (30). Our present results may support previous findings suggesting that levels of MCP expression are increased in some cell lines by cytokines and inflammation (31,32).…”
Section: Urinary Cd46 In Glomerulonephritissupporting
confidence: 90%
“…Another report (29) has suggested that tubular MCP is overexpressed at the deposition site of the membrane attack complex. The levels of sMCP were increased in patients with malignancy (19) and autoimmune diseases such as systemic lupus erythematosus (30). Our present results may support previous findings suggesting that levels of MCP expression are increased in some cell lines by cytokines and inflammation (31,32).…”
Section: Urinary Cd46 In Glomerulonephritissupporting
confidence: 90%
“…5), whereas there was no growth difference in serum from these mice (data not shown), indicating that human CD46 facilitates bacterial survival and suggesting that the binding of CD46 might help the bacteria to survive host defenses. It was shown that soluble CD46 is present in normal human plasma (18) and that CD46 levels are elevated under autoimmune conditions (12,25). To investigate the importance of CD46 in human blood, we pre- (10 7 CFU) in lag, early log, mid-log, or stationary phase was incubated for 2 h with MBP-CD46 or MBP (control).…”
Section: Resultsmentioning
confidence: 99%
“…2C), skews nTregs and Tconv to Tr1 secreting IL-10, which prematurely imbalances the adaptive immunity toward immune suppression. The role of C3b protein, the CD46 agonist resulting from C′ activation, in the pathogenesis of active lupus patients is also suggested by the presence in the serum of these patients of soluble CD46 (30), product of proteolytic cleavage of apoptotic cell membranes (31). As for IFN-α, by reducing nTreg and Tconv number and function, this cytokine may further enhance the risk of autoimmunity and infection.…”
Section: Discussionmentioning
confidence: 99%